Exercise as Medicine in Migraine: Clinical Outcomes, Mechanisms, and Long-Term Therapeutic Potential - Łyżwa, Julia; Strzępek, Aleksandra; Majchrzyk, Aleksandra; Chmurska, Agnieszka; Janaszek, Agnieszka; Frączek, Karolina; Smerdzyński, Mateusz; Kałwa, Natalia; Kałuża, Kinga; Pater, Michał (Journal of Education, Health and Sport, 2026)
Background. Migraine is a highly disabling neurological disorder affecting approximately 14.4% of the global population. Its pathophysiology involves the activation of the trigeminovascular neuroinflammatory cascade and central sensitization. While pharmacological treatments are standard, issues with tolerability and medication overuse necessitate effective non-pharmacological interventions. Aim. To synthesize current clinical evidence (2019–2025) regarding the impact of structured physical activity on migraine pathophysiology, clinical outcomes, and craniocervical dysfunction. Material and Methods. A systematic review was conducted via PubMed/MEDLINE, covering articles from January 2019 to March 2026. The analysis included clinical trials, meta-analyses, and systematic reviews focusing on adult populations with episodic or chronic migraine. Results. Moderate-intensity continuous training (MCT) remains the clinical gold standard, reducing migraine frequency by a mean of 0.6 days/month and attack duration by 20–27%. Combined aerobic and resistance training demonstrates the highest efficacy in reducing overall migraine burden. Exercise induces analgesia by stimulating the release of endogenous opioids and endocannabinoids, promoting anti-inflammatory modulation, and stabilizing cortical excitability. Addressing craniocervical impairments through the Flexion-Rotation Test and multimodal physiotherapy significantly reduces disability. Tele-rehabilitation and digital tools further enhance long-term adherence. Conclusions. Structured physical activity is a potent, low-risk intervention for migraine prophylaxis. A minimum therapeutic window of 10–12 weeks is required for significant clinical improvement. Furthermore, exercise acts synergistically with modern pharmacological agents, such as CGRP antagonists, to improve global sensorimotor function and quality of life.